Proses Berpikir Reflektif Siswa SMP Bergaya Belajar Pragmatis Dalam Memecahkan Masalah Pada Materi Bangun Ruang Sisi Datar - Yuniar Ika Putri Pranyata; Rosita Dwi Ferdiani (Universitas Mathla'ul Anwar Banten, 2021)
This study will reveal the nature of the Reflective Thinking Process of Junior High School Students with Pragmatic Learning Style in Solving Problems in Curved Side Space Building Materials. This research was conducted in MTs. Miftahul Ulum Ngembal, Pasuruan. The research subjects were 9th grade students of MTs. Miftahul Ulum Ngembal, Pasuruan. The number of subjects in this study amounted to 2 MTs students with pragmatic learning style. Researchers in this qualitative research, act as the main instrument. While the supporting instruments in this study were in the form of test sheets, questionnaires, and interview guidelines. The results showed that: 1) In the Reacting phase. In the reacting phase, subject 1 was not able to mention in detail what was known but was able to mention what was asked and was unable to explain in detail the relationship between what was asked and what was known. While subject 2 is able to mention in detail what is known and what is being asked, and is able to explain in detail the relationship between what is asked and what is known. 2) In the Comparing phase. In this phase, subject 1 is able to explain the answers to the problems obtained, remember the formula used to answer the questions, and be able to relate the problems asked to the problems at hand. While subject 2 is able to remember the formula needed, but unable to apply it to the problem. So there is an error in answering the question. 3) In the Contemplating phase. In this phase, both subjects were able to detect errors and truths, and were able to correct errors. But at the time of concluding, subject 1 could conclude correctly, and subject 2 could not conclude correctly, because of errors made during the comparing phase.